19-Hydroxy-bufalin, a major bufadienolide isolated from the parotoid gland secretions of the Panamanian endemic toad Rhinella centralis (Bufonidae), inhibits the growth of Trypanosoma cruzi. (15th April 2020) - Rodriguez, Candelario; Ibáñez, Roberto; Ng, Michelle; Spadafora, Carmenza; Durant-Archibold, Armando A.; Gutiérrez, Marcelino
Abstract: American trypanosomiasis is a parasitic neglected disease, responsible for the death of approximately 10, 000 people every year. Amphibians are recognized for producing in their cutaneous glands substances with pharmacological potential against a variety of pathologies. Here we investigated the antiprotozoal activity against Trypanosoma cruzi of bufadienolides isolated from the parotoid glands secretions of the toad Rhinella centralis from Panama. NMR and mass spectrometry analysis led to the identification of the active compound 19-hydroxy-bufalin, for which its antitrypanosomal activity and occurrence in the genus Rhinella are reported for the first time. This compound showed low cytotoxicity and significant selectivity which confers to it a potential role for the treatment of Chagas disease. Highlights: A metabolite was isolated from the parotoid gland secretion of the toad Rhinella centralis . 19-hydroxy-bufalin is reported for the first time in the genus Rhinella . 19-hydroxy-bufalin presented potent activity against Trypanosoma cruzi with low cytotoxicity and significant selectivity.